ADAB PESERTA DIDIK DALAM KITAB TA’LIMUL MUTA’ALLIM; PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Andry Fitriyanto; Hermansyah; Aning Sri Mintarsih (Journal of Research and Thought on Islamic Education (JRTIE), 2025)
Islamic education serves not merely as a means of knowledge transmission but also as a medium for character formation and moral habituation through the principle of ta’dīb (the cultivation of adab). In the modern context, the erosion of student ethics toward educators reflects a weakening of adab internalization, which constitutes the moral foundation of Islamic education. At the same time, public debates have emerged over the teacher–student relationship within pesantren (Islamic boarding schools), following a controversial report aired by a national television network (Trans7) that portrayed pesantren education as feudalistic. This controversy illustrates the interpretive gap between outsiders and insiders, showing that understanding traditional religious and educational practices requires hermeneutical wisdom to avoid biased judgments. Within this context, examining Ta‘līm al-Muta‘allim through a philosophical lens becomes crucial, as the text remains a central reference in pesantren education and embodies a value system linking knowledge, morality, and spirituality in the teacher–student relationship. This study adopts a qualitative-philosophical approach through the library research method. Primary data are drawn from the original text of Ta‘līm al-Muta‘allim and its classical commentaries, while secondary sources include modern literature on Islamic educational philosophy and Ibn Miskawayh’s theory of values. The analysis proceeds through three main stages: conceptual description, philosophical interpretation, and axiological reflection, aiming to uncover the ethical meaning and relevance of adab in the context of contemporary Islamic education. The findings reveal that al-Zarnūjī positions adab as the spirit of education—a guiding moral value that renders knowledge both blessed and ethically meaningful. Principles such as sincerity, discipline, respect for teachers, and self-control are viewed as forms of riyāḍah al-nafs (spiritual training) that direct learners toward moral perfection. Through the axiological framework of Ibn Miskawayh, these principles are interpreted as the cultivation of virtue (al-faḍīlah) and the attainment of inner harmony (tawāzun al-nafs) through the balance of intellect, emotion, and desire. The synthesis of al-Zarnūjī’s and Ibn Miskawayh’s ideas emphasizes that the ultimate aim of Islamic education extends beyond intellectual achievement to the formation of morally refined and spiritually balanced individuals. Its relevance today lies in its ability to offer a moral framework that harmonizes rationality and spirituality within the educational process. Thus, revitalizing the concept of adab through an axiological perspective provides a strategic foundation for reconstructing Islamic education rooted in wisdom, integrity, and humanity.